Stability analysis of existing tunnels under dynamic loads during excavation of new tunnels - Hao Li; Sichun Long; Xiangen Lai; Lijun Kuang; Jian Zhou; Mengguang Liao; Chaofeng Zeng (Scientific Reports)
Abstract Understanding the deformation mechanism and behaviour of adjacent tunnels subjected to dynamic train loads provides vital technical insights for engineering design. This study conducted a detailed analysis and revealed that tunnel excavation significantly affects the stability of adjacent existing tunnels under dynamic loads. First, we developed a dynamic load simulation approach and derived a calculation formula for shield-soil friction. A methodology for analyzing the stress in the surrounding rock of the tunnel was established. Subsequently, the impact of dynamic loads on the stability of existing tunnels was assessed through numerical simulations. Finally, the numerical results were compared with field-measured data to validate the reliability of the research findings. The results indicated that, compared to the condition without train load, the maximum vertical and lateral displacements at the vault of the existing tunnel under dynamic load condition increased by 2.9 mm and 1 mm, respectively, leading to an overall safety and stability coefficient reduction of approximately 0.1. Furthermore, the influence of dynamic loads on the stability of the existing tunnel intensified with increasing train speeds under various load conditions. For train speeds of ≤ 40 km/h, the dynamic load could effectively be considered as a static load. Notably, the surrounding soft rock exhibited a higher degree of stress release compared to the surrounding hard rock. The stresses at the soft-hard rock interface were found to potentially induce damage to the tunnel. In scenarios where new and existing tunnels were in proximity, the dynamic load was incorporated into the entire simulation process, yielding results that closely aligned with actual measurements.